Demographic Pattern of Covid 19 cases in and around Vijayawada, Andhra Pradesh - Ravimuni.K; Srinivasu Rao Palagani; Usha Rani.K (Institute of Medico-legal Publications Pvt Ltd, 2021)
COVID-19 Pandemic has brought a threatening challenge to the world and as well as for Indian societyand economy. In India, it has become a public health disaster and its’ intensity increasing continuously.For the disaster risk reduction, and capacity building against the COVID-19 pandemic understanding ofthe relationship between socio-environmental conditions with the pandemic is very necessary. India is the2nd largest country in terms of population and 6th leading economy in the world. This study represents thehospitalized patients with COVID?19. In this cohort, significantly more patients admitted to hospital werefound to be in lower socioeconomic groups. patients with comorbidities should take all necessary precautionsto avoid getting infected with SARS CoV-2, as they usually have the worst prognosis. These precautionsinclude regular handwashing with soap and water or use of alcohol-based hand sanitizer, limiting person-toperson contact and practicing social distancing, wearing a face mask in public places, and overall limitinggoing to public areas at this time unless it is necessary